Ensino-aprendizagem por projetos em artes visuais: práticas no 4º ano do ensino fundamental - Silva, Hellen Caroline (2020)
The purpose of this research was to investigate the processes that lead to the elaboration and execution of a teaching-learning project in visual arts, considering that the actions and reflections developed in the research sought to contribute to the teaching practice, in the search of a contemporary approach to learning. The choice of project methodology was due to the fact that this proposal allows both the teacher and the student to be active in teaching and learning, articulating content, life and experiences; in addition to being a practice that values research, and contributes to the critical and reflective development of students. The execution of the teaching-learning project was developed in a municipal school in Uberlândia - MG, in two classes of the 4th year of elementary school I, during the entire academic year of 2019, where Art became a way to raise students' awareness in classroom about the importance of developing attitudes of conservation of the environment that surrounds us.